STRATEGI MENINGKATKAN KEMAMPUAN MENULIS KARANGAN KREATIF PADA SISWA KELAS 4 DAN 5: Studi Multikasus di MIN Rejotangan dan SDN 1 Rejotangan Tulungagung - Ika Setiawati (LP2M IAIN Tulungagung, 2016)
One of the main tasks of a teacher is conducting learning effective and engaging for students. To realize that is certainly a teacher should have specific strategies. Like wise with the task to create a creative article on the students. Creative article is one of the tips to train students to explore ideas and instill love to read and write. And so it should be socialized early start elementary school level. This research, used qualitative research with multicase studies and the objects in two primary schools: MIN Rejotangan and SDN 1 Rejotangan Tulungagung. As a result, creative writing strategies developed by applying the media and a variety of learning methods with regard KD being discussed.Keywords: Strategy, Creative Writing, Elementary School